2016
DOI: 10.1089/ars.2015.6484
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of the Manganese Photoactivated Carbon Monoxide-Releasing Molecule [Mn(CO)3(tpa-κ3N)]+Against a PathogenicEscherichia colithat Causes Urinary Infections

Abstract: Aims: We set out to investigate the antibacterial activity of a new Mn-based photoactivated carbon monoxide-releasing molecule (PhotoCORM, [Mn(CO)3(tpa-κ3N)]+) against an antibiotic-resistant uropathogenic strain (EC958) of Escherichia coli. Results: Activated PhotoCORM inhibits growth and decreases viability of E. coli EC958, but non-illuminated carbon monoxide-releasing molecule (CORM) is without effect. NADH-supported respiration rates are significantly decreased by activated PhotoCORM, mimicking the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 73 publications
4
51
0
Order By: Relevance
“…For example, Nobre et al reported that the administration of CO gas into the growing cultures could cause significant impairment to the growth of Escherichia coli and Staphylococcus aureus . Recently, CORMs with the capacity of delivering CO directly to intracellular targets have been used as bactericides against a wide range of microorganisms, such as Pseudomonas aeruginosa , Mycobacterium tuberculosis , Helicobacter pylori , pathogenic Escherichia coli , and Neisseria gonorrhoeae . Importantly, CORMs were shown to be more potent bactericides than CO gas due to the accumulation of CORMs inside bacterial cells .…”
Section: The Application Of Co In Disease Therapymentioning
confidence: 99%
“…For example, Nobre et al reported that the administration of CO gas into the growing cultures could cause significant impairment to the growth of Escherichia coli and Staphylococcus aureus . Recently, CORMs with the capacity of delivering CO directly to intracellular targets have been used as bactericides against a wide range of microorganisms, such as Pseudomonas aeruginosa , Mycobacterium tuberculosis , Helicobacter pylori , pathogenic Escherichia coli , and Neisseria gonorrhoeae . Importantly, CORMs were shown to be more potent bactericides than CO gas due to the accumulation of CORMs inside bacterial cells .…”
Section: The Application Of Co In Disease Therapymentioning
confidence: 99%
“…as model systems for known manganese based metalloenzymes like Mn-catalase, arginase 8,9 or the OEC in PSII. 7,10 To probe this concept, we additionally investigated the light-triggered CO substitution for the Mn I -carbonyl complex 3, which is also already well investigated as photoCORM 11 and for its therapeutic use, 12 bearing the potentially tetradentate trispyridylmethylamin (tpa) ligand, for which µ-oxido bridged Mn III /Mn IV complexes of high catalase activity have already been reported. 13…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, the results showed promising steps for the use of photoCORMs as drug templates for the treatment of breast cancer. Tinajero and coworkers reported an Mn-based photoactivated CORM which reduces growth and viability of Escherichia coli, only by light induction [56]. They demonstrated that CO binds to specific intracellular sites, namely, respiratory oxidases and a globin protein expressed in a particular strain, while the Mn metal center is not accumulated in the cells.…”
Section: Uv Light Photoactivated Cormsmentioning
confidence: 99%